Kajian Kebutuhan Air Irigasi Tanaman Jagung (Zea mays L.) Berdasarkan KP-01 dan Metode Thornthwaite-Mather - Wahyuni, Sri; Kendarto, Dwi Rustam; Bafdal, Nurpilihan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2019)
Two different methods for determining irrigation water requirement for corn, is  KP-01 and  Thornthwaite-Mather method. Two Methods have different parameter such as reference crop evapotranspiration (ETo) and effective rainfall. The average ETo value using Penman-Monteith for Thornthwaite-Mather was lower (82,5%) than using Penman Modification method (KP-01) . The ratio of effective rainfall between KP-01 and Thornthwaite-Mather was 33,02%.  Corn water irrigation requirement for a pattern planting based on KP-01 is 806,96 mm, while corn water irrigation requirement based on Thornthwaite-Mather method is 254,4125 mm.  Corn water irrigation requirement using KP-01 is higher than Thornthwaite-Mather because effective rainfall method for KP-01 (using USDA Soil Conservation Service) is lower than rainfall effective for Thornthwaite-Mather.